Perbandingan Kualitas Layanan Antara Bank Syariah Dengan Bank Konvensional Ditinjau Dari Kepuasan Nasabah Di Kabupaten Pacitan - Mansur Azis (ACTIVA: Jurnal Ekonomi Syariah, 2018)
This research aims to make data services between Sharia Bank and Conventional Bank in Pacitan Regency in terms of customer satisfaction. Satisfaction on the service quality is viewed from the five service dimensions such as responsiveness, assurance, tangible, empathy and reliability. The data in this study were obtained from questionnaires of customer satisfactions over the service quality between Sharia and Conventional banks. Afterwards, by using random sampling, it was found 4 feasible samples; 2 Sharia Banks and 2 Conventional Banks. The analysis technique used to see the comparison of service quality between Sharia Bank and Conventional Banks was the ANAVA method. The analysis conducted in the study showed that there were differences in the level of satisfaction between Sharia Bank and Conventional Bank in Pacitan Regency, yet it was not quite significant. There were significant interactions over the influence of service quality towards customer satisfactions which were showed that the higher service quality, the better customer satisfactions. The customers satisfaction of Conventional Bank was not higher than the customers satisfaction of Sharia Bank in groups that received high quality services, Sharia Bank satisfaction was not better than Conventional Bank satisfaction in groups of customers who received low quality services in Pacitan Regency.